Distance Effect Between Four Elliptical Pipes With Ratio Of 0,8 On The Pressure Arround Pipes - Astuty Hadjar (Journal of Mechanical Science and Engineering, 2017)
Tube is a component of a heat exchanger tube is usually in the form of a small circle section pipe. But do not rule out the possibility of tube using a pipe that is not circle section for example an elliptical section to aims pressure as small as possible, because of the pressure resistor is small, the resulting pressure drop means smaller. Pipes used are a modification AW wavin pipe with an outside diameter of 6 cm into the elliptical section pipe with a ratio of 0.8. Tests carried out in Test engine Subsonic Wind Tunnel Section 40, two pipe by measuring angles and two more be used to measure variations in the distance between the pipes. From the test results obtained by the value of the pressure difference (ΔP) and temperature (°C), the value obtained is inserted into the equation calculation in order to get the coefficient of pressure (CP) getting bigger, but the speed (U) and the pressure coefficient resistor (CDP) smaller as increasing the distance between the pipes.